Evaluation of Phenolic Content, Antioxidant Activity and Cytotoxic Effects of Ulva lactuca and Hypnea musiformis Marine Algae on MDA-MB-468 Cell Line - Alireza Moulazadeh; Razieh Ranjbar; Amin Dakhili Ardestani; Aref Keshavarzi; Fatemeh Karimzadeh; Maryam Rahnavard; Zahra Zarei Jeliani; Sohrab Najafipour (Fasa University of Medical Sciences, 2021)
Background & Objective: Breast cancer is one of the leading causes of death among women around the world. Attempts to find alternative therapies continue due to therapeutic resistance, side effects, and the high cost of conventional treatments. Materials & Methods: Hydro-methanolic extract of Ulva lactuca and Hypnea musiformis marine algae was prepared by maceration method. The phenolic content of these extracts was compared using the standard Folin-Ciocateu method and the antioxidant capacity was evaluated by the FRAP method. The cytotoxic effects of algae were compared using MTT assay and morphological changes were evaluated by an inverted microscope. Results: The phenolic content of Hypnea musiformis extract (12.46 ± 1.19 µg GAE/mg, P<0.0001), and its antioxidant activity (203.03 ± 27.87 µmol Fe2+/g, P= 0.007), was significantly higher than that of the alga Ulva lactuca. The cytotoxic effects of Hypnea musiformis extract were concentration and time dependent and had severe morphological changes on the cells. Algae extract of Hypnea musiformis (1000 µg/ml) inhibited 84.79 ± 4.66 of % cell proliferation after 72 hours of treatment. The IC50 value of cytotoxic effect of Hypnea musiformis and Ulva lactuca on MDA-MB-468 was respectively 701.2 and >1000 µg/ml after 72h incubation. Conclusions: Hypnea musiformis had higher cytotoxic effects than Ulva lactuca on MDA-MB-468 cells, probably due to its higher phenolic content and antioxidant capacity. Therefore, it appears that a Hypnea musiformis alga is a better option to continue research on drug discovery of anticancer compounds.